Limits of applicability of the weakly relativistic approximation in the theory of plasma waves - Pavlov, S.S.; Castejón, F. (Вопросы атомной науки и техники, 2018)
The more general weakly-relativistic plasma dispersion functions are introduced and discussed in the frame of the fully relativistic approach for the theory of plasma waves.